Olympic Games 2020: Discourse of the Japanese Government after Postponed in japantimes.co.jp (Jurnal Kajian Media, 2021)
The COVID-19 outbreak had succeeded in making the holding of the 2020 Tokyo Olympic Games postponed. This became heartbreaking news when Japan was almost ready to host the 32nd Olympic Games. This was the second in Japan during the Olympic Games, which was held in the 1940 Olympic Games but had to be canceled because Japan was still at war with China since 1937. This research aims to find out the discourse of the Japanese government on 2020 Olympic Games in the mid of COVID-19 outbreak after postponed. The method used in this research is the analysis of van Dijk's critical discourse on online news in japantimes.co.jp after the implementation of the tokyo 2020 Olympic Games was finally announced on March 24, 2020 to be postponed. The findings in this study are that during the postponement of the 2020 Olympic Games the Japanese government tried to use the time to stabilize economic conditions in the midst of the 19th COVID outbreak and use the time to make the Tokyo Olympic Games become the greatest Olympic Games event of all time.Keywords: Olympic Games 2020; Discourse; Japanese Government; COVID-19; Postponed.